Nursing at work and the challenges of being on the frontline of COVID-19 (Research, Society and Development, 2022)
The large number of cases of people with COVID-19 caused mass concern, which had serious repercussions on health services. This research aims to elucidate scientific evidence that addresses the difficulties and impacts faced at work by nursing professionals working on the front line of the COVID-19 pandemic. This is an integrative literature review based on the methodological recommendations Preferred Reporting Items for Systematic Reviews and Meta-Analyses – PRISMA. The selection of articles was carried out from December 2021 to February 2022. The databases used in the study were: Virtual Health Library (VHL), Latin American and Caribbean Literature (Lilacs), Medical Literature Analysis and Retrieval System Online (MedLine). We found 20 articles that were directly linked to the theme, 1 article in LILACS and 19 articles in MEDLINE, totaling 20 works, analyzed regarding their relationship with the theme and in the end they were limited to 10 articles. The pandemic brought with it many challenges, including maintaining the number of professionals, but with the high risk of contamination, many get sick, needing to be away from work, which causes overload, longer exposure time and psychological pressure for other professionals who end up suffering with the accumulation of activities. It is concluded that the impacts and challenges experienced by frontline nursing professionals directly affect mental and psychological health, bringing serious difficulties to their workplace, in addition to those already provided by the work environment itself.